Career Expectations, Difficulties And Choices In Nursing Students: A Cross- Sectional Study - Wahyudi, Andri Setiya; Tristiana, Dian; Dewi, Lingga Curnia; Asmoro, Candra Panji; Sari, Ni Putu Wulan Purnama; Sulistyono, R Endro (International Journal of Psychosocial Rehabilitation, 2020)
This study aimed to explore and compare between career expectations and difficulties in deciding careers and career choices in nursing students. This study was a cross-sectional study in an university in Surabaya, Indonesia, conducted with 233 first and final year bachelor degree nursing students, using a range of instruments: Career Expectations Questionnaire, Career Decision Difficulties Questionnaire, and Questionnaire Survey on Career Choice. The data were then tested by t-test and Mann Whitney. The results showed no significant differences between first and final year students for career expectations, career decisions and career choices. Different aspects between first and final year students were in the aspects of organizational membership (p=.029) and there were differences in difficulties in deciding career, especially in aspects of lack of readiness (p=.031). The learning process and experience during the study period can be related to the impact of students’ confidence in deciding their chosen careers. Support from academic staff and the environment such as parents, friends and nursing organizations are needed to shape positive aspects of the careers chosen by students.